MANAJEMEN RISIKO PENGELOLAAN DANA TABARRU’ PADA ASURANSI PEMBIAYAAN PT ASURANSI JIWA SYARIAH AL AMIN KEDIRI PERSPEKTIF MANAJEMEN RISIKO ISLAM - Arlupi Madyasari (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
Risk in a sharia perspective is a risk deviation from sharia principles, for example the risk in the afterlife that everything that humans do in this world will be rewarded with heaven or hell. World risks, namely negligence, lies which will become obstacles in achieving the goals set in accordance with Islamic sharia. The purpose of this research is to find out how Islamic risk management is implemented by PT Asuransi Jiwa Syariah Al Amin Kediri in managing tabarru' funds. The method used in this research is qualitative with the type of case study research by means of observation, interviews and documentation. The results of this research include risk management of tabarru' funds in financing insurance products at PT Asuransi Jiwa Syariah Al Amin Kediri carried out by means of risk identification by means of underwriting limits, risk ranking by means of level of complexity, risk control by self-retention and response to risks that significantly through product and investment diversification, changes in reinsurance scheme rates and risk financing. From a risk management perspective, PT Asuransi Jiwa Syariah Al Amin Kediri Islam is planning every month to avoid gharar being carried out such as when launching a new product the contract is always intended with the intention of tabarru' aiming to provide funds of sincerity for insurance participants who have a disaster